2019
DOI: 10.1371/journal.pcbi.1006941
|View full text |Cite
|
Sign up to set email alerts
|

A multi-state model of the CaMKII dodecamer suggests a role for calmodulin in maintenance of autophosphorylation

Abstract: Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) accounts for up to 2 percent of all brain protein and is essential to memory function. CaMKII activity is known to regulate dynamic shifts in the size and signaling strength of neuronal connections, a process known as synaptic plasticity. Increasingly, computational models are used to explore synaptic plasticity and the mechanisms regulating CaMKII activity. Conventional modeling approaches may exclude biophysical detail due to the impractical number of st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…However, it did significantly prolong the lifetimes of CaMKII-bound CaM4, CaM2C, and CaM2C1N. In an an earlier modeling study (Pharris et al, 2019), it was noted that the CaM-binding domain on CaMKII overlaps significantly with the region on the CaMKII regulatory domain immediately downstream of T-286, near where PP1 would bind to catalyze dephosphorylation of T-286. Therefore, they suggested that bound CaM might block or partially inhibit reversal by PP1 of CaMKII autophosphorylation.…”
Section: Resultsmentioning
confidence: 93%
“…However, it did significantly prolong the lifetimes of CaMKII-bound CaM4, CaM2C, and CaM2C1N. In an an earlier modeling study (Pharris et al, 2019), it was noted that the CaM-binding domain on CaMKII overlaps significantly with the region on the CaMKII regulatory domain immediately downstream of T-286, near where PP1 would bind to catalyze dephosphorylation of T-286. Therefore, they suggested that bound CaM might block or partially inhibit reversal by PP1 of CaMKII autophosphorylation.…”
Section: Resultsmentioning
confidence: 93%
“…It also remains unclear experimentally whether stable E-LTP can be achieved by the biochemical activity of CaMKII and PP. Although many modeling simulations observe and implement steady states of the CaMKII & PP system ( 52 55 ), newer findings show that the stable plasticity does not have to rely on the stability of the fully activated state of CaMKII ( 35 , 56 , 57 ). Here, we focus on modeling the induction of early LTP/D, over the first several minutes.…”
Section: Discussionmentioning
confidence: 98%
“…Most previous models of STDP [and all models of BTSP] are phenomenological descriptions of the strengthening/weakening of synapses, including the STDP work ( 58 , 59 , 60 ) [and the BTSP work ( 61 , 62 )]. Notable exceptions are the works of ( 28 , 57 ), which model in some detail the biochemical reactions of CaMKII. Our model of the biochemistry in the PSD begins from the detailed model of the activation of CaMKII of ( 28 ) but with several enhancements: First, to model the binding and disassociation of molecules and how they influence phosphorylation and dephosphorylation, we replace Michaelis–Menten schemes (quasi-steady-state) with quasi-equilibrium representations, which are a more fundamental description of the catalytic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a rule-based model was used to interpret single-molecule detection of multisite phosphorylation on intact EGFR to reveal a new role for the abundance of adapter proteins to redirect signaling 65 . Given the challenges with representing the various activation states of a 12-subunit Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) holoenzyme that is essential for memory function, a rule-based model identified a molecular mechanism stabilizing protein activity that was obscured in prior reduced models 66 . Inspired by engineering better CAR T cells, Rohrs et al developed a rule-based model to interpret site-specific phosphorylation dynamics associated with Chimeric Antigen Receptors 67 .…”
Section: Discussionmentioning
confidence: 99%